1991
DOI: 10.1128/jb.173.1.204-210.1991
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of Bacillus subtilis cell walls: effects of ions and lysozyme

Abstract: Bacterial threads of BacUlus subtilis have been immersed in, and redrawn from, water of various pH values, in solutions of (NH4)2SO4 and NaCI of various concentrations, and in Iysozyme solutions. The changes in the tensile strength, elastic modulus, and other mechanical properties of the bacterial cell wall due to these treatments were obtained. The data show that change in pH has little effect but that as the salt concentration is increased, the cell walls become more ductile. A high salt concentration (1 M N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…This transition decreases the elastic modulus and strength of the fibres and increases the strain. In addition, water is associated with accessory polymers containing ionisable and hydrophilic groups222331.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition decreases the elastic modulus and strength of the fibres and increases the strain. In addition, water is associated with accessory polymers containing ionisable and hydrophilic groups222331.…”
Section: Resultsmentioning
confidence: 99%
“…stretched bacterial threads and measured the Young’s modulus of the cell wall as well as other mechanical properties of the bacterial cells92021. The threads in their study contained 20,000 parallel fibres from division-suppressed mutant of B. subtilis 2223. However, their test results for these bacterial threads are not suitable for predicting the mechanical properties of the cell wall and individual cellular fibres.…”
mentioning
confidence: 99%
“…Washed threads had the same compact and highly aligned structure as did threads drawn from culture medium (see Fig. 4A of the accompanying paper [23] and also Fig. 4 (lower) of reference 21) but lacked the coating of TB medium residue (clearly visible in Fig.…”
Section: Methodsmentioning
confidence: 96%
“…On the other hand, the external cell wall could experience rupture due to the applied stress exceeding the fracture tolerance limit. Experiments have indicated that the tensile strength of bacteria is approximately 300 MPa with a Young's modulus on the order of 13 GPa (Thwaites et al, 1991). We note that the PA populations appear to have altered characteristics, including the external shape and size of the bacteria (R. Hazael, P.F McMillan et al, in prep).…”
Section: Discussionmentioning
confidence: 78%
“…Understanding the mechanical behavior and time-dependent deformation behavior of living cells subjected to mechanical loading is becoming an important area in soft matter biophysics, with implications for medical and nanomaterials research (Bonakdar et al 2016;Vadillo-Rodriguez andDutcher, 2011, Fabry et al 2001;Thwaites et al;1991). Most living cells show a viscoelastic deformation response that follows a power law in time (Bonakdar et al 2016;Fabry et al 2001;).…”
Section: Discussionmentioning
confidence: 99%